Interrupting base-mediated benzofuran ring transformation with michael acceptors - Srinivas, Kolluru; Sharma, Rashmi; Ramana, Chepuri V. (Journal of Organic Chemistry, 2017)
A simple two-stage approach for the synthesis of 3-(2-arylbenzofuran-3-yl)propanoates and propanamides has been developed employing simple acrylates and acrylamides and readily available 3-aroylbenzofurans. The key step of this process involves a base-mediated ring opening of the 3-aroylbenzofurans and subsequent Michael addition of the resulting 1,3-dicarbonyl intermediate with acrylate/acrylamide, followed by the deformylation in one-pot. The resulting products undergo an acid-mediated dehydrative cyclization to arrive at these targets.
Keywords: Acyl Benzylic Bromides; Beta-Ketoaldehydes; Efficient Synthesis; Ortho-Hydroxybenzyl Ketones; Phenols; Position; Precursors; Sur Le Benzofuranne; Transposition